Public sentiments towards the use of Wolbachia-Aedes technology in Singapore - Liew, Christina (2022)
Wolbachia technology is a novel vector control approach that can reduce mosquito populations and the risk of mosquito-borne diseases, which has recently gained popularity amongst countries. In 2016, Singapore embarked on a multi-phased field study named Project Wolbachia - Singapore, to evaluate the use of Wolbachia technology as an Aedes aegypti mosquito population suppression tool to fight dengue. Due to the novelty of this technology in Singapore, this study aims to understand the public's acceptance and sentiments towards the use of Wolbachia technology.